Prognostic indicators among laboratory data on arrival to assess the severity of mamushi bites - Takeuchi, Ikuto (J Rural Med, 2019)
Objective: This study aimed to retrospectively determine which laboratory data on arrival for patients with mamushi bites was useful to predict the severity of mamushi bites. Materials and Methods: The subjects were divided into the following two groups: the mild group included subjects with mamushi bites Grades I and II, while the severe group included subjects with mamushi bites Grades III, IV, and V. The subjects’ variables were compared between the two groups. Results: There were no significant differences between the two groups regarding the levels of hematocrit, total protein, alanine aminotransferase, aspartate aminotransferase, creatinine phosphokinase, blood urea nitrogen, creatinine, and international normalized ratio of prothrombin time on arrival. Moreover, white blood cell count and platelet count on arrival in the mild group were significantly lower than those in the severe group. Furthermore, activated partial thromboplastin time on arrival was significantly higher in the mild group than in the severe group. Multivariate analysis using white blood cell count and platelet count and level of activated partial thromboplastin time revealed the following significant prognostic indicators of severity of mamushi bites: white blood cell count (Log Worth, 2.1; p<0.01) and platelet count (Log Worth, 1.6; p<0.05). Conclusion: White blood cell count and platelet count on arrival of patients with mamushi bites are considered significant prognostic indicators in determining the severity of mamushi bites.